2015
DOI: 10.1016/j.foodpol.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Grain subsidy, liquidity constraints and food security—Impact of the grain subsidy program on the grain-sown areas in China

Abstract: This study examined the effects of China's grain subsidy program, the largest food self-sufficiency project in the developing countries, on grain-sown areas within a context of liquidity constraints. A large household level panel was used to evaluate how the subsidy affects the cultivation schedule of farm households through the relaxation of households' liquidity constraints. Results suggest that in general, the grain subsidy program significantly improved farm householdsÕ grain planting areas for liquidity-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 30 publications
3
88
0
1
Order By: Relevance
“…However, due to the technological progress and heavy use of chemical fertilizer and pesticides, China's grain production presented a growth trend during the past decades [47][48][49]. Nevertheless, the significant urbanization-related agricultural land loss has a positive correlation with grain production decrease and partly threatens food security in some developed areas.…”
Section: Correlation Between Urbanization-related Agricultural Land Lmentioning
confidence: 99%
“…However, due to the technological progress and heavy use of chemical fertilizer and pesticides, China's grain production presented a growth trend during the past decades [47][48][49]. Nevertheless, the significant urbanization-related agricultural land loss has a positive correlation with grain production decrease and partly threatens food security in some developed areas.…”
Section: Correlation Between Urbanization-related Agricultural Land Lmentioning
confidence: 99%
“…Liu [25] conducted an empirical study of a direct food subsidy policy in Shandong Province to analyze the efficiency of policy implementation in different regions. Yi et al [26] argued that, in general, the grain subsidy policy contributes to improvements in farm households' grain planting areas in liquidity-constrained households. In addition, Ito [27] applied a stochastic frontier output distance function to investigate the rationality of Chinese farmers' crop selection and found strong evidence that the Chinese policy of grain self-sufficiency exemplifies the technical and allocative efficiencies of agricultural production.…”
Section: Agricultural Subsidiesmentioning
confidence: 99%
“…Meng (2012) found that the grain subsidy can keep farmers from engaging in migratory work, indicating that it may improve grain production. Yi, Sun and Zhou (2015) found that the grain subsidy can increase grain planting areas for liquidity-constrained households. Our interviews of farmers and field observations suggest that subsidies to rice producers in general are not large enough to alter the relative economic returns from rice cultivation and non-farm income, and therefore we should not expect a significant impact on grain production, agreeing with Gale, Lohmar and Tuan (2005).…”
Section: Tablementioning
confidence: 99%
“…Most of these studies use an econometric approach. Econometric models, e.g., Yi, Sun and Zhou (2015), are powerful in identifying general patterns, especially when large, representative samples are used. However, they generally lack in-depth understanding of causal mechanisms.…”
Section: Tablementioning
confidence: 99%